MAKING A PERSONAL APPLICATION SITE USING MACROMEDIA FLASH V. 5.0 - Harry Ardhany; Hariyanto Hariyanto, S.Kom.,MMSI. (Jurnal Sistem Informasi, 2003)
In writing this scholarly discussion about creating a site that at the time of the current era of globalization of science and technology developments in the computer field is very rapid. The development site (website) has been extremely rapid and is still ongoing in line with developments in technology especially information technology. Information obtained from the website (website) is very much and the latest such as: political, social, cultural. Where is extremely influential in the lives of many aspects, both directly and indirectly. There are still many services and facilities contained on the website, also there are many more that might be created in the future. In connection with the development of computer technology, the authors are interested in creating a personal website using Macromedia Flash Version 5.0 program. So that there is a personal site can provide its own solutions to the public.